Training needs of teachers in emergencies (Journal of Hama University, 2025)
Summary:The research aimed to identify the most important training needs for teachers in emergency situations, The researcher followed the descriptive analytical approach, where she prepared a questionnaire consisting of four axes: (crisis management, digital skills, first aid, and psychological and social support), distributed over (41) items, and the original population consisted of all basic education teachers in the Hama Education Directorate, and a random sample of (376) male and female teachers was taken, and the results showed that there were high training needs for teachers in all axes according to the order (psychosocial support, first aid, digital skills, crisis management), The results also showed that there were no differences in these needs due to the variables of gender and academic qualification, and that there were differences due to the variable of years of experience for teachers with less than ten years of experience.
Keywords: Keywords: training needs – basic education teachers – emergency situations